Cost effectiveness of cord blood versus bone marrow and peripheral blood stem cells - Thomas Bart (Dove Medical Press, 2010)
Thomas BartSwiss Blood Stem Cells, Bern, SwitzerlandAbstract: Umbilical cord blood (CB) has become, since its first successful use more than two decades ago, an increasingly important source of blood stem cells. In this light, an overview of current usage of CB in the field of unrelated hematopoietic blood stem cell transplantation (HSCT) is given. The three main sources of hematopoietic stem cells: bone marrow (BM), peripheral blood stem cells (PBSC), and cord blood (CB) are compared as regards their current quantitative usage in HSCT. A cost analysis of the named three hematopoietic blood stem cell (HSC) sources, taking into account various factors, is undertaken. The health economical comparison shows significant differences between CB on the one side, and BM and PBSC on the other. The consequences for the public health side and propositions for a possible health care policy, especially regarding future resource allocation towards the different choices for HSCT products, are discussed. An outlook on the possible future usage of BM, PBSC, and CB and its implications on health systems, donor registries, and CB banks is given.Keywords: health economy, cord blood, hematopoietic stem cell transplantation